An introduction to environmental studies - Turk, Jonathan (Saunders, 1985)
This book is the elucidation of principles, not the advocacy of specific political policies. Major themes, such as the relationship between environmental quality and the human condition, the nature of environmental problems, uncertainties in the prediction of future trends, the interplay belems, uncertainties in the prediction, the role of the legal system in environmental management, the assessment of risk, and the constraints imposed by the laws of nature, are introduced in the two chapters.